Dysfunctions in Mice by NMDA Receptor Point Mutations NR1(N598Q) and NR1(N598R) - Single, Frank N. (J Neurosci, 2000)
NMDA receptors in mice were mutated by gene targeting to substitute asparagine (N) in position 598 of the NR1 subunit to glutamine (Q) or arginine (R). Animals expressing exclusively the mutatedNR1 alleles, NR1(Q/Q) andNR1(−/R) mice, developed a perinatally lethal phenotype mainly characterized by respiratory failure. The dysfunctions were partially rescued in heterozygous mice by the presence of pure wild-type receptors. Thus, NR1(+/Q) mice exhibited reduced life expectancy, with females being impaired in nurturing; NR1(+/R) mice displayed signs of underdevelopment such as growth retardation and impaired righting reflex, and died before weaning. We analyzed the key properties of NMDA receptors, high Ca(2+) permeability, and voltage-dependent Mg(2+) block, in the mutant mice. Comparison of the complex physiological and phenotypical changes observed in the different mutants indicates that properties controlled by NR1 subunit residue N598 are important for autonomic brain functions at birth and during postnatal development. We conclude that disturbed NMDA receptor signaling mediates a variety of neurological phenotypes.